Impact of a single educational session on oral hygiene practices among children of a primary school of Meerut, India - Pawan Parashar; Sartaj Ahmad; Amir Maroof Khan; Rupesh Tiwari (Healthcare in Low-resource Settings, 2013)
Oral health promotion through schools is recommended by the World Health Organization (WHO) for improving knowledge, attitude, and behavior related to oral health and for prevention and control of dental diseases among school children. In low resource settings, it is important to develop evidence for health education methods in oral health behavioral practices. The objectives of this study were to assess both the baseline awareness and practices regarding oral hygiene and the impact of a single education session on the change in oral health behavior. A school based, cross-sectional study on 112 primary school children was conducted after obtaining the consent of the school authorities and parents. A pretested, structured proforma was used for baseline awareness and behavior regarding oral health. A 30 min educational session was imparted and after 1 month, and the oral health practices were reassessed to find out the impact of the education session. Baseline survey revealed the following findings. Self-reported dental problems were found in 48.22% of the children in the last 6 months. When asked about the risk factors for dental problems, 28.57% mentioned eating sweets followed by improper brushing, whereas 40.17% were not aware about any risk factor for dental problems. It was found that 28.57% of the children did not brush their teeth regularly, whereas 35.71% used a tooth-brush for brushing their teeth. After the intervention, it was observed that there was a significant improvement in the proportion of children using a toothbrush for cleaning their teeth and of those who rinsed their mouth after meals. In conclusion, even a single education session was found to be effective in bringing about a change in the oral health behavior of primary school children.